Deaden talks through Bones about their Final Fate: A Case Report - Naveen Sharma; Kuldeep Kumar; Priti Singh; Lalit Chopra; Naresh Kumar; Pradeep Yadav (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Skeletonization of body is a complex process. Solving a suspected crime is multidisciplinaryapproach, which requires experts from the various specialities. Various methods are employed to commit crimesthroughout the world. Many cases of homicide remain unsolved due to misleading, lack of suspicion, incompleteor inadequate investigations.Methods: In present case post mortem examination of a skeletonised body was conducted by the authors,identification and apparent cause of which after inquest was impossible for investigating agencies. Usually, it isdifficult toopined cause, manner and time since death with certainty in the such corpse when body devoid of softtissue. In present case authors opined the cause, manner and time since death in a skeletonisedand partially burntbody. Which will help the investigators to find out the perpetrator.Conclusion: A post mortem examination of a corpse by the experts is mandatory for the identification, collectionand preservation of trace evidences to correlate the victim, accused, scene of incidence and suspected weapon ofoffence.